Micro-watershed Treatment - a Case Study of Restoring Degraded Forests - Singh, H. S. (Indian Forester, 1998)
Soil and moisture conservation along with water harvesting works in degraded area help in exploiting the full potential of the regeneration of the existing vegetation as well as planted seedlings of suitable species, thus making the difficult task of rehabilitation of degraded forests achievable. Treatment and afforestation of denuded forest should be planned on the basis of structure and characteristic of micro-watershed which is the smallest functional unit of the land. 92 ha of the degraded forests of micro watershed was developed by harvesting the entire rain water facilitating the development of vegetation from the existing regeneration stock i.e. root stock and supplementing the plantation of many suitable species to restore the forest similar to the natural forest existed in the past. Improved sub-soil moisture in the area due to construction of contour trenches, nala bundings, and eight earthen checkdams brought tremendous changes by transforming the area devoid of vegetation to a dense young forest with rich flora in four years. The micro-watershed treatment programme in Golawada forest is now considered a model restoration work and has become an important centre for education and training for visitors.